The Effect of Business Capital, Length of Business and Entrepreneurship Attitude to The Income and Welfare of The Family Women of Batik Craftsmen in Danau Teluk Jambi City - Rafida Era Era (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2019)
This study aims to determine: (1) the effect of venture capital , length of business , and entrepreneurial attitudes on the income of batik craftsmen partially (2) the effect of venture capital , length of business , and entrepreneurial attitudes on the income of batik craftsmen simultaneously , (3) the effect of income on the welfare of batik craftsmen , and (4) the influence of venture capital, business duration, and entrepreneurial attitude towards the income of batik craftsmen through income variables . This type of research is quantitative descriptive research. The population is batik artisans in Danau Teluk Jambi city with 74 batik craftsmen. Data were collected with a questionnaire that was tested for validity and reliability. Data analysis techniques used are multiple regression analysis and path analysis. The results showed that: (1) there was a positive and significant influence of venture capital on the income of batik craftsmen, with a significance of 0.0 00 <0.05; and regression coefficients of 0, 905; there is a positive and significant influence of business duration on the income of batik craftsmen, with a significance value of 0,000 <0.05; and a regression coefficient of 0.990; there is a positive and significant effect of entrepreneurial attitudes on the income of batik craftsmen, with a significance value of 0.0 34 <0.05; and a regression coefficient of 0.286 and (2 ) there is a significant influence of joint venture capital, length of business, and entrepreneurial attitude towards the income of batik craftsmen , with a significance value of 0,000 <0.05; and R 2 amounted to 89.4 %. ; (3) The effect of income on family welfare is positive at 0.005 but not significant because the significance value is 0.223 <0.05, this means the income variable is not an intervening variable; (4) The effect of business capital on welfare through income is 0.0045, the effect of business profits on welfare through income is 0.00495, the effect of entrepreneurial attitudes on welfare through income is 0.00143.